RESOURCE SHARING IN THE DIGITAL ERA: PERSPECTIVES AND PRACTICES IN PHILIPPINE ACADEMIC LIBRARIES - Garcia, Justina P.; Peñaflor, Janice D.C. (Journal of Philippine Librarianship, 2019)
Libraries have long been engaging in collaborative and resource sharing initiatives in order to provide the information needs of their patrons. The digital age and the perennial issue on inadequate funding have made this practice even more necessary. In the Philippines, several networks of libraries or consortia have sprung up with the primary purpose of promoting collaboration and cooperation. This is so because participating in a consortium offers the advantage of gaining access to more resources and services. This study examines the extent of resource-sharing practices of the Network of CALABARZON Educational Institution Library Committee (NOCEILC), a consortium with 19 institution-members from the five Philippine provinces. It employs survey and interview method to find out the different types of collaborative activities the member-libraries engage in and their level of satisfaction with these consortial endeavors. This paper also attempts to find out the challenges that confront the libraries in their resource sharing efforts as well as the potential solutions to these issues. The results of the study provide useful information on how NOCEI member libraries collaborate and share their resources, which generally mirrors the current collaborative resource sharing practices of the academic libraries in the Philippines.
Keywords: resource sharing; consortium; collaboration; academic libraries; Network of CALABARZON Educational Institution (NOCEI)